Incidental Inguinal Tubercular Lymphadenitis in a female of Androgen Insensivity Syndrome- A rarest of rare presentation - Paridhi; Shalini Bahadur; Madhuvan Gupta; Shalini Shukla; Shivani Kalhan; Deepak Goel; Deeksha Singh; Vivek Gupta (Journal of Pathology of Nepal)
Androgen insensitivity syndrome (AIS) is a rare X-linked recessive disorder occurring in phenotypic women with male genotype (46, XY) resulting due to mutation in the X chromosome. On the other hand, tuberculosis (TB) is a chronic granulomatous infection caused by Mycobacterium tuberculosis, an acid-fast bacillus. We report a case of a 22-year-old unmarried female presenting with bilateral inguinal pain and primary amenorrhea, which, on comprehensive evaluation, revealed complete female external genitalia and intra-abdominal testes. The karyotype was 46 XY, hence a diagnosis of complete AIS was made. One of the ‘probable testes’ removed surgically was an inguinal lymph node with tuberculous lymphadenitis. Isolated inguinal tuberculous lymphadenopathy, by itself, is rare. Co-occurrence of Complete AIS and inguinal tuberculous lymphadenopathy is a highly unusual and rare association that has not been documented in the literature reviewed.